Chiclets versus XClé: uma análise multimodal das marcas no processo de disputa legal - Kreutz, Elizete de Azevedo; Silvestre, Carminda (Language and Law / Linguagem e Direito, 2019)
In 2006 Cadbury Adams Brasil Ltda, owner of the trademark Chiclets, filed a lawsuit against Docile Alimentos Ltda, demanding the revocation of their trademark XClé for infringement. Drawing examples from this trademark dispute we present a theoretical framework and its technical basis to present the argument which enabled the defendant to win the case. We interpret language within the perspective of Social Semiotics with a focus on multimodality and set out to demonstrate its usefulness with examples from trademark disputes in identifying links between Law, Linguistics and Semiotics. Using a nationally well-known Brazilian trademark as an example we will show through a focus on naming and packaging how a multimodal analysis can be used to defend against a charge of trademark infringement.